BOOKLET PENCEGAHAN DIABETES MELITUS DAN PENGETAHUAN DIET REMAJA SEBAGAI UPAYA PENCEGAHAN DINI DIABETES MELITUS TIPE 2 - Windha Widyastuti; Siti Rofiqoh; Isyti’aroh Isyti’aroh; Siti Khuzaiyah (Edu Masda Journal, 2021)
The increase in the incidence of Diabetes Mellitus at a young age is associated with lifestyle changes that are currently increasingly irregular as well as inappropriate eating patterns. Lack of knowledge about diet related to the risk of Diabetes Mellitus also plays a role. This study aims to determine how the effect of education with booklets on adolescent knowledge about diet related to the risk of Diabetes Mellitus. This quasi-experimental research used a one group pre-post test design. The instruments used were questionnaires and booklets about diet related to the risk of Diabetes Mellitus, that analyzed by Wilcoxon test. The research location in the Wonopringgo Health Center area in Pekalongan Regency. The research sample was obtained based on cluster random sampling, with a number of 38 teenagers who attended in the youth integrated service post (posyandu) from March to April 2021. The results showed that there was a positive effect of providing education using booklets with knowledge of diet related to the risk of Diabetes Mellitus in adolescents (p = 0.000). This study concludes that educational booklets can be used to increase knowledge of diet related to the risk of Diabetes Mellitus from an early age, so it is hoped that this booklet can be used for early diabetes prevention both in schools and any other services among adolescents.ABSTRAKPeningkatan kejadian Diabetes Melitus diusia muda dikaitkan dengan perubahan gaya hidup yang dewasa ini semakin tidak teratur seperti halnya pola makan yang tidak sesuai. Kurangnya pengetahuan akan pola makan yang terkait dengan resiko Diabetes Melitus turut berperan . Penelitian ini bertujuan mengetahui bagaimana pengaruh edukasi menggunakan Booklet terhadap pengetahuan remaja tentang pola makan terkait resiko Diabetes Melitus. Penelitian quasi eksperimen ini menggunakan  desain  one group pre-post test design.  Instrumen yang digunakan adalah kuesioner dan booklet tentang pola makan terkait resiko Diabetes Melitus, dengan analisa data menggunakan uji wilcoxon. Lokasi penelitian di Wilayah Puskesmas Wonopringgo,  Kabupaten Pekalongan. Sampel penelitian diperoleh berdasarkan  cluster random sampling, sejumlah 38 remaja yang hadir di posyandu remaja pada bulan Maret sampaiApril 2021. Hasil menunjukkan adanya pengaruh positif pemberian edukasi menggunakan booklet dengan pengetahuan pola makan terkait resiko Diabetes Melitus  pada remaja (p= 0,000). Studi ini menyimpulkan bahwa edukasi booklet dapat digunakan untuk meningkatkan pengetahuan pola makan terkait resiko Dibetes Melitus sejak dini, sehingga diharapkan Booklet ini dapat dimanfatkan untuk pencegahan Diabetes sejak dini baik di sekolah sekolah maupun pelayanan pada remaja lainnya